MODEL KONSELING BERBASIS BUDAYA GUSJIGANG: KERANGKA KONSEPTUAL MODEL KONSELING BERBASIS KEARIFAN BUDAYA LOKAL KUDUS - Edris Zamroni (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2015)
This article discusses the development of a conceptual framework gusjigang counseling model as a form of local wisdom Kudus Regency society. Gusjigang is fiolosofi life teachings of the Sunan Kudus that teaches people to be good at behaving, smart thinking and could trade. Gusjigang counseling model is also affedted with the nuances of Islamic counseling that emphasizes the values of Islamic religious teachings in the order of the famous Kudus religious communities. The counseling goal is to develop a noble character to humans, fosters systematic and scientific thinking skills as well as improve the tenacity, creativity, ability to innovate in order to survive.